Comparison of Press Freedom from a Legal Perspective A Study of Indonesia and Norway - Anastasya Regina Sekar Cahyanto; M rizki Yudha Prawira (Dinasti Research, 2026)
This study compares the protection of press freedom in Indonesia and Norway from a legal perspective. This study aims to identify how the mechanism for protecting press freedom in Norway serves as a best practice and assess its relevance in the context of implementing the system and strengthening press freedom protection in Indonesia. The method used in this study is normative juridical with a comparative approach to laws and regulations. This study employs a literature-based data collection method, analyzing primary, secondary, and tertiary legal materials. The results show that Norway has strong protections for press freedom through constitutional guarantees, transparent information disclosure, and state-protected press mechanisms. On the contrary, Indonesia already has an adequate legal basis, but its implementation still faces the problem of the criminalization of journalists. This study provides an overview of how Norway, with stronger legal mechanisms to protect their press freedom, can serve as a reference for Indonesia.